(untitled) (Journal of Foreign Language Studies, 2019)
When mentioning sensitive topics in communication, people tend to use indirect words and phrases so as to avoid making listeners, even speakers, embarrassed. These words and phrases are called ‘euphemism’. Euphemisms are formed and used differently in each language worldwide based on socio-cultural conditions. This article focuses on analyzing euphemisms for ‘death’ in Thai language from a perspective of language and culture, helping Thai learners have a deeper look at features of Thai euphemisms and avoid unpleasant and impolite communication.